Hyperuricemia in Acute Coronary Syndrome Patients at Tertiary Care Hospital Peshawar. - Shafiullah, Shabina; Abbas, Muhammad; Abdur Rauf, Muhammad; Tahir Shah, Syed; Saleem Awan, Muhammad; Ziyad, Muhammad (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Objective To investigate the affiliation between elevated uric acid and acute coronary syndrome. Methods This descriptive cross-sectional study was conducted over twelve months from June 2022 to May 2023 in the Cardiac Care Unit (CCU) and Pathology Laboratory of Kuwait Teaching Hospital. 201 patients were included, determined using the WHO sample size calculator. Inclusion criteria were patients with typical ischemic chest pain indicative of ACS, irrespective of gender and age, who were willing to participate. Data were collected using a structured preform questionnaire covering demographics, medical history, clinical presentation, and diagnostic findings. Key data included patient age, gender, history of hypertension, diabetes, hyperlipidemia, smoking status, family history of coronary artery disease, and symptoms at presentation. ACS was classified into STEMI, NSTEMI, or Unstable Angina based on ECG and troponin-I levels. Serum uric acid levels were measured after an eight-hour fasting period. Data were entered into Microsoft Excel and analyzed using SPSS version 25, employing descriptive statistics and Chi-square tests, with a p-value of <0.05 considered significant. Results A total 201 study participants were enrolled (average age: 57.5 years), with 99 (49%) males. Diabetes mellitus was found in 88 (44% of patients) and hypertension in 83 (41%). In 73 (36%) of the patients, hyperuricemia was seen. Males were more likely to have hyperuricemia (75%) than females 60 (59%), and diabetics were more likely to have it (80%) than hypertensive people 59 (71%). The overall incidence of hyperuricemia in ACS patients was 52%. Conclusion Our findings demonstrate the high prevalence of hyperuricemia in persons diagnosed with acute coronary syndrome. Routine monitoring and surveillance of blood uric acid levels in the general population appears to be a viable technique for proactively identifying and addressing anomalies promptly.